Extending the Spectrum of Radiological Findings in Patients With Severe Osteopetrosis and Different Genetic Backgrounds. Issue 7 (10th March 2016) - Simanovsky, Natalia; Rozovsky, Katya; Hiller, Nurith; Weintraub, Michael; Stepensky, Polina
Abstract : Purpose: To evaluate radiological findings in a cohort of 22 patients with infantile malignant osteopetrosis in order to establish the correlation between radiological findings and different genetic backgrounds. Materials and Methods: Clinical files, genetic analysis results, and radiological examinations of children treated for osteopetrosis with bone marrow transplantation in a referral center in the last 5 years were retrospectively evaluated. The study received institutional review board (IRB) approval. Results: Twenty‐two patients were included in the study: 18 males, four females, ages 1 month–9 years 10 months, and the median age was 11 months (mean 23 months). There were 12 patients with different mutations in the TCIRG1 gene, five with mutations in the SNX10 gene, four children harbored RANK mutations, and one patient had a CLCN7 mutation. We noted more severe radiological findings in patients with TCIRG1 and RANK mutations, including fractures, osteopetrorickets, hydrocephalus, and hepatomegaly. Varus deformity of the femoral neck was seen exclusively in patients with a TCIRG1 mutation. Conclusions: The variable genetic spectrum of osteopetrosis is associated with a variable radiological presentation. These correlations may be helpful for priorities in genetic analysis.